On the Structure of Complex Variable Struve and Modified Struve Function of the Second Kind - Pog, Tibor K.; Pons, Stanley (Journal of Nepal Mathematical Society, 2025)
In this note we derive explicit expressions for real and imaginary parts of the Struve function Kν(z) of the second kind and also the modified Struve function Mν(z) of the second kind of real parameter ν and complex variable z. The derivation method is based on trigonometric-type differentiation operators. The outcomes resolve the problem of the